Interaction techniques for mobile collocation - Lucero, Andrés; Quigley, Aaron; Rekimoto, Jun; Roudaut, Anne; Porcheron, Martin; Serrano, Marcos (2016)
Research on mobile collocated interactions has been exploring situations where collocated users engage in collaborative activities using their personal mobile devices (e.g., smartphones and tablets), thus going from personal/individual toward shared/multiuser experiences and interactions. The proliferation of ever- smaller computers that can be worn on our wrists (e.g., Apple Watch) and other parts of the body (e.g., Google Glass), have expanded the possibilities and increased the complexity of interaction in what we term “mobile collocated” situations. The focus of this workshop is to bring together a community of researchers, designers and practitioners to explore novel interaction techniques for mobile collocated interactions.